Toxicidade e deterrência de extratos pirolenhosos e óleos vegetais sobre Liriomyza sativae (Diptera: Agromyzidae) - Pereira, Jéssica Barboza (2023)
Mining flies belong to the genus Liriomyza, and they exhibit extensive polyphagy, which causes irreparable losses in plant species. The most severe impacts caused by the pest are associated with its larval stage. The increase in the number of insecticide applications as well as doses above the recommendation aimed at efficiency in con trolling the pest can lead to the emergence of populations with resistance. The objec tive of this work was to develop methods aimed at sustainable management for L. sativae using (1) pyroligneous extracts (2) Vegetable oils and respective emulsions. For the toxicity test, solutions were prepared at different concentrations by diluting them in distilled water, leaf discs containing L. sativae larvae were immersed in the solution. For insect activity and deterrence tests, jack bean plants were subjected to airbrush treatments, sprayed with 6 mL of the solutions on each plant. It was verified through the results that (1) the pyroligneous extracts caused mortality in three-day-old leafminer larvae, with emphasis on the coffee straw extract at 350ºC. (2) Fixed neem oil and its association with citronella were efficient during the developmental stages of the leafminer fly. The emulsion enhanced the effectiveness of the oils. It is concluded that pyroligneous extracts and vegetable oils are effective against the leafminer fly. The use of emulsions has been shown to be capable of enhancing the effect of oils, representing a promising strategy for the management of L. sativae